Investigação dos efeitos do ultrassom terapêutico e laser na osteoartrite e a participação das células da glia espinais na nocicepção em camundongos - Malta, Iago Henrique Silva (2019)
Osteoarthritis (OA) is a musculoskeletal disorder that affects the joints and is the most prevalent of the joint diseases. OA is multifactorial and the most common pain symptom is pain. It is known that, in addition to joint pathology, central mechanisms contribute to intensify pain in patients with OA. Spinal glial cells have been investigated in OA, and they play an important role in OA-induced nociception. Physiotherapeutic resources, such as therapeutic ultrasound (US) and laser therapy (LASER), have been widely used in clinical practice because they produce anti-inflammatory and antinociceptive effects in several disorders, including OA, and are almost free of adverse effects Therefore, the objective of this study was to investigate the effects of US and LASER on OA-induced nociception and also to assess the participation of glial cells in the nociception through pharmacological experiments in mice. Male Swiss mice weighing between 35 and 45 g were used. For the induction of OA, the received a single intra-articular (i.a.) injection of 3.4 mg/Kg of monosodium iodoacetate (MIA). The mechanical nociceptive threshold was evaluated by the von frey filaments test for 21 days. Clinical parameters of gait, temperature and articular diameter were also evaluated. The participation of microglia and spinal astrocytes in OA-induced nociception was evaluated. For this, animals with OA and control animals were injected intrathecally (i.t.) on the 14th day with minocycline (a microglial inhibitor) or fluorocitrate (an astrocyte inhibitor) at the doses of 0.001 mg/Kg and 0.002 mg/K of minocycline or 5 nmol/Kg and 10 nmol/Kg of fluorocitrate. In addition, animals with OA and control animals were treated daily over 21 days with either US (1 MHz, 1 W/cm 2, continuous, 5 minutes) or LASER (830 nm, continuous, 2 points of 8 J/cm 2). The duration of the effects of a single treatment with US or LASER on the 14th day was also evaluated. It was verified that the i.a. injection of MIA caused nociception from the third day until the 21st day compared to the control group. The i.t. injection of both of minocycline and fluorocitrate reversed the OA-induced nociception, suggesting that spinal glial cells participate in the nociception. Daily treatment with US attenuated the OA-induced nocicetion from the 14th to the 21st day of treatment, while LASER attenuated nociception in the 3rd, 10th and 14th day of evaluation. Single treatment with US or LASER on the 14th day had an antinociceptive effect that lasted for one hour after the application. No differences in joint temperature and diameter were observed during the experiment, nor were there any significant changes in gait. According to the results, we conclude that OA causes nociception and glial activation, the physiotherapeutic agents promoted antinociception when applied daily, and the present nociceptive model did not cause any changes in gait or joint temperature and diameter.